High step‐up SVMC‐based DC/DC converter for offshore wind farms. Issue 6 (6th March 2019) - Zhu, Binxin; Liu, Song; Vilathgamuwa, Don Mahinda; Li, Yang
Abstract : This study presents a high step‐up scalable voltage multiple cell (SVMC)‐based DC/DC converters, which have the features of high gain, low and adjustable components stresses and automatic input‐current sharing in each input phase. In virtue of the above features, the converter is applicable for the DC collection grids for offshore wind farms. In this study, the converter in terms of working principle and property characteristics are analysed with four input phases and three SVMCs. The converter has also been evaluated in terms of the component stress and voltage conversion ratio against some other converters for high‐power occasions. Moreover, a 2.5 MW simulation model and a 1.2 kW prototype were constructed for verification.